2023
DOI: 10.1093/ntr/ntad133
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sociodemographic, Clinical, and Genetic Factors to Aid Alaska Native and American Indian People to Successfully Quit Smoking

Jaedon P Avey,
Krista R Schaefer,
Carolyn J Noonan
et al.

Abstract: Introduction Alaska Native and American Indian (ANAI) people have a smoking prevalence of 23%. Nicotine metabolite ratio (NMR) and genetic testing may enable tailored selection of tobacco cessation medication. The purpose of this study was to evaluate the relative contributions of NMR, cessation medication, demographics, and tobacco use history to cessation. Methods Participants were recruited into an observational cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A recent observational study of AI/AN adults starting the Quit Tobacco Program (QTP) at Southcentral Foundation found that 28% of participants demonstrated slow nicotine metabolism (NMR < 0.31), 66% had normal nicotine metabolism (NMR ≥ 0.31), and 6% had an NMR that was unquanti able (either cotinine or 3-hydroxycontinine values were < 1.5 ng/mL at baseline). 9 Of the total sample, 24% were smoking-abstinent at six weeks. A combined group of people with slow metabolism who used NRT and people with normal metabolism who used varenicline had a quit rate of 36.5%, a 13% higher quit rate than in the total sample.…”
Section: Introductionmentioning
confidence: 99%
“…A recent observational study of AI/AN adults starting the Quit Tobacco Program (QTP) at Southcentral Foundation found that 28% of participants demonstrated slow nicotine metabolism (NMR < 0.31), 66% had normal nicotine metabolism (NMR ≥ 0.31), and 6% had an NMR that was unquanti able (either cotinine or 3-hydroxycontinine values were < 1.5 ng/mL at baseline). 9 Of the total sample, 24% were smoking-abstinent at six weeks. A combined group of people with slow metabolism who used NRT and people with normal metabolism who used varenicline had a quit rate of 36.5%, a 13% higher quit rate than in the total sample.…”
Section: Introductionmentioning
confidence: 99%